Introduction to Narrative Phenomenon Model: A Framework for Mapping War Stories that Travel through Generations - Dahal, Chandi Raj (Bodhi: An Interdisciplinary Journal, 2019)
This article relies upon cultural trauma theory for the basic understanding of storytelling in a post-traumatic situation and presents its findings based on researcher’s own observation of a post conflict situation of decade long armed conflict in Nepal. It introduces a communication model to explain the storytelling phenomenon that emerges during and after any violent situation and that exists through newer generations. First, the article discusses some theories related to trauma stories and sociology of generational differences. Second, it proposes Narrative Phenomenon Model as a new tool that can map the journey of trauma stories created by those exposed to war or violent events. Third, it discusses how narratives get created, modified or transformed into multiple truths.